Trust and motivation in the health sector : a systematic review - Okello, Dickson R O (Department of Public Health and Family Medicine, 2015)
Supporting improved performance of health workers is vital in health system strengthening. There are several factors that have been identified as playing key roles in influencing health worker performance. Motivation of HWs is one of the areas for improving delivery of health care services, yet it is under investigated. Moreover, the mechanisms underlying the interactions between motivation and other variables such as workplace trust relations are largely unknown. This dissertation is organised into three parts. Part A is the review protocol which outlines the background and the review methodology. A qualitative systematic review approach is adopted and literature search of the five chosen databases is conducted using keywords and phrases derived from the review question. Defined inclusion and exclusion criteria are used to identify and select suitable articles. An appropriate tool is then used to appraise selected articles which are then subjected to thematic analysis. Part B is a literature review of existing empirical and theoretical work on health worker motivation. It provides the background to the systematic review in Part C. It defines the word motivation as used in the health sector, and then explores empirical work on health worker motivation using an appropriate conceptual framework. The literature review further summarises and concludes on the possible link between trust and motivation in the health sector.